2022
DOI: 10.1021/acsmaterialsau.1c00045
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation and Stability Testing of Perovskite Solar Cells for Real Life Applications

Abstract: With the progress in the development of perovskite solar cells, increased efforts have been devoted to enhancing their stability. With more devices being able to survive harsher stability testing conditions, such as damp heat or outdoor testing, there is increased interest in encapsulation techniques suitable for this type of tests, since both device architecture compatible with increased stability and effective encapsulation are necessary for those testing conditions. A variety of encapsulation techniques and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 131 publications
0
58
0
Order By: Relevance
“…It can be observed that there is a significant difference in the films prepared from 2PPABr+PbI 2 and 2PPAI+PbBr 2 , indicating that the precursors used affect the mixing in the final film with a shift possibly occurring either due to internal strain or due to differences in mixing at nanoscale. Finally, it should be noted that at high illumination powers and/or temperatures the encapsulation of the samples plays an important role, since delamination can occur . As shown in Figure S14, using a cover glass held together with clips (method previously reported) results in an erroneous result of suppression of segregation (likely due to increased ion diffusion due to partial solvation due to moisture ingress), while segregation followed by remixing with a significant intensity drop is obtained with epoxy-only encapsulation, and finally, no remixing is observed when edges of the epoxy+cover glass encapsulated sample are additionally sealed by tape.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…It can be observed that there is a significant difference in the films prepared from 2PPABr+PbI 2 and 2PPAI+PbBr 2 , indicating that the precursors used affect the mixing in the final film with a shift possibly occurring either due to internal strain or due to differences in mixing at nanoscale. Finally, it should be noted that at high illumination powers and/or temperatures the encapsulation of the samples plays an important role, since delamination can occur . As shown in Figure S14, using a cover glass held together with clips (method previously reported) results in an erroneous result of suppression of segregation (likely due to increased ion diffusion due to partial solvation due to moisture ingress), while segregation followed by remixing with a significant intensity drop is obtained with epoxy-only encapsulation, and finally, no remixing is observed when edges of the epoxy+cover glass encapsulated sample are additionally sealed by tape.…”
mentioning
confidence: 70%
“…Finally, it should be noted that at high illumination powers and/or temperatures the encapsulation of the samples plays an important role, since delamination can occur. 43 As shown in Figure S14, using a cover glass held together with clips (method previously reported 18 ) results in an erroneous result of suppression of segregation (likely due to increased ion diffusion due to partial solvation due to moisture ingress), while segregation followed by remixing with a significant intensity drop is obtained with epoxy-only encapsulation, and finally, no remixing is observed when edges of the epoxy+cover glass encapsulated sample are additionally sealed by tape. At room temperature, epoxy+cover glass encapsulation is sufficient and reliable, but a simple cover glass held together with clips is not, as illustrated in Figure S15.…”
mentioning
confidence: 82%
“…These include polymers deposited via spin coating, Al 2 O 3 derived by atomic layer deposition or plasma enhanced atomic layer deposition, Si 3 N 4 , SiO 2 synthesized using plasma enhanced chemical vapor deposition, and parylene‐C using chemical vapor deposition. [ 89 ] Key requirements for the material/process selection are to avoid using harmful solvents in the encapsulant, low temperature deposition method, and the layer to be chemically inert with respect to the layers underneath. [ 90 ] Glass–glass encapsulant with the use of an adhesive for rigid substrate applications, that is, building integrated OPVs, has been reported as one of the most efficient encapsulants with water vapor transmission ratio less than 10 −6 g m −2 day −1 .…”
Section: Emerging Pv Technologiesmentioning
confidence: 99%
“…15–18 Nowadays, encapsulation is a possible forefront of long-term usage of HP solar cells and other devices. 19–21…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] Nowadays, encapsulation is a possible forefront of long-term usage of HP solar cells and other devices. [19][20][21] A common approach to studying the stability of PSCs is to track how a gure of merit (e.g., the open-circuit voltage, shortcircuit current density, and the power conversion efficiency) varies with time when submitted to a given condition. [22][23][24][25] In this sense, major concerns have been establishing standard aging conditions for PSCs.…”
Section: Introductionmentioning
confidence: 99%